Mind the gender gap: The social neuroscience of belonging - Rippon, Gina (Frontiers in Human Neuroscience, 2023)
Gender gaps persist in the 21st century, in many aspects of society and in many types of organisation. There are pay gaps in almost all domains, reports of glass ceilings and the ‘missing middle’ in business, finance, law and politics, and dramatic under-representation of women in many branches of science, even in the most ‘gender equal’ countries. This is despite decades of effort to address them, including targeted legislation and many Diversity and Inclusion initiatives Early essentialist, competence-based explanations for the existence of gender gaps have been largely discredited at the research level, although their persistence in the public consciousness and at the level of education and training can still negatively bias both individual self-belief and organisational processes. Contemporary essentialist explanations are now emerging, with claims that such gaps are the manifestations of the presence or absence of endogenous, brain-based characteristics underpinning career progression or career preferences. The focus remains on the individual as the source of gender imbalances. Less attention has been paid to the contextual aspects of organisations where gender gaps are evident, to inclusion (or the lack of it), or the availability of unbiased reward and progression pathways. Advances in 21st century social cognitive neuroscience are revealing the importance of external organisational processes as powerful brain-changing forces, with their potentially negative impact on self-belief and a sense of belonging. Key research is demonstrating the cortical and behavioural consequences of negative social experiences, with the activation of core inhibitory pathways associated with low self-esteem, lack of engagement and eventual withdrawal. This paper will argue that reference to such research will provide better explanations for the persistence of gender gaps, and offer evidence-based insights into addressing gender gap issues. Importantly, this is not a rejection of an endogenous, brain-based explanation for gender gaps but the elaboration of a better-informed 21st century model, flagging up the need to take factors such as cultural stereotyping and organisational bias into account in any drive towards true gender equity, or genuinely levelled playing fields.